2015
DOI: 10.12968/bjon.2015.24.sup10.s15
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of people with progressive advanced cancer

Abstract: Cancer is a long-term, life-limiting condition, and its end-of-life stage is complex. This study aimed to understand the lived experience of patients with progressive advanced oncological disease. Seven women in an acute hospital in Portugal were interviewed and the results analysed using a phenomenological approach to understand their lived experience. The analysis indicated that lived experience of these patients has six essential constituents: information about one's own health; perception of the disease; e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
2
0
2
Order By: Relevance
“…Similar psychological distress was reported in a study done in Ethiopia among cervical cancer patients during follow-up care [21]. Hopelessness and lack of emotional support reported in the current study have also been reported by other studies done in different settings [14,29,31] where cancer was perceived as a death sentence for diagnosed patients. Public awareness programs are required to address such information gaps and rule out prevailing misconceptions concerning cervical cancer and other cancerous diseases in general [12].…”
Section: Discussionsupporting
confidence: 89%
“…Similar psychological distress was reported in a study done in Ethiopia among cervical cancer patients during follow-up care [21]. Hopelessness and lack of emotional support reported in the current study have also been reported by other studies done in different settings [14,29,31] where cancer was perceived as a death sentence for diagnosed patients. Public awareness programs are required to address such information gaps and rule out prevailing misconceptions concerning cervical cancer and other cancerous diseases in general [12].…”
Section: Discussionsupporting
confidence: 89%
“…All selected studies were scrutinized and some were excluded at this stage because of not being retrievable online, being written up in a language other than English or German, taking the form of a meta-analysis or review, or because of there being a lack of clarity regarding the extent to which participants’ cancer was advanced and therefore could be considered terminal. One further study (Esteves, Roxo, & Saraiva, 2015) was excluded because the presentations of its findings was merged with a review of other studies’ findings, which made it difficult to extract themes specific to Esteves, Roxo, & Saraiva’s own data.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Ellis et al (2015) found that patients suffered when being faced with their own mortality, but also, this suffering altered their view on life fundamentally and made them capable of discovering what was important for them in life. As to patients' emotional reactions during illness, Esteves et al (2015) found that patients transitioned into experiencing emotional instability, which involved emotions of fear, anger, anxiety, hopelessness and also on the contrary: acceptance, hope, a will to live and fight the disease. Furthermore, a study by Morgan et al (2017) found that patients experienced constant transitions related to their own bodily decline, which involved their bodies becoming unfamiliar, unpredictable and vulnerable.…”
Section: A C C E P T E Dmentioning
confidence: 99%